PERMODELAN SPASIAL WATER POVERTY INDEX DENGAN INFRASTRUKTUR DAN KONDISI SOSIAL KECAMATAN DONOMULYO - Ryan Alfi Marcellino; Ismu Rini Dwi Ari; Septiana Hariyani (Department of Urban and Regional Planning, Faculty of Engineering, Universitas Brawijaya, 2023)
Donomulyo sub-district is one of the priority region to water scarce and clean water infrastructural priority programme, this area only has 23% coverage of piped clean water management. Reinforced by the water poverty index (WPI) which classified Donomulyo as unsafe to critical level for clean water availability. Water poverty value also influenced by other variabels such as social matter, according to social network analysis (SNA) showed area with lower value of WPI also has a lower value of SNA. Hence, this paper will explain the correlation between the water poverty index (Y) to social (X1) and infrastructure (X2) using spatial regression. Spatial regression used in this case to prove the correlation between dependent variable (WPI) and independent variables (infrastructure and social) with spatial aspect, thus obtained a close or significant correlation (α<0,05) among WPI value along with the well user ratio and households with septic tank in accordance with SNI ratio value. Depending on this model people of Donomulyo district should lessen the number of well user and improve the ratio of households with septic tank in accordance with SNI in order to improve WPI status.